2009
DOI: 10.4314/thrb.v11i1.43242
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anaemia among HIV-infected patients in Benin City, Nigeria

Abstract: Abstract:The aim of this study was to use the World Health Organization (WHO) definition of anaemia to determine prevalence of anaemia among human immunodeficiency virus (HIV)-infected patients on the highly active antiretroviral therapy (HAART) and those that are HAART naive. Haemoglobin concentration was measured in 457 HIV patients consisting of 217 patients on HAART (86 males and 131 females) and 240 HAART naive patients (106 males and 134 females). According to WHO criteria, anaemia was defined as a haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
38
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 8 publications
15
38
6
1
Order By: Relevance
“…This probably indicates improvement in hemoglobin after ART. This observation was in concordance with study conducted by Omoregie et al Mathews et al and Thulasi et al, [15][16][17] the prevalence of anemia in their studies was as shown in above table.…”
Section: Evaluation Of Hematological Parameters Rbc Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…This probably indicates improvement in hemoglobin after ART. This observation was in concordance with study conducted by Omoregie et al Mathews et al and Thulasi et al, [15][16][17] the prevalence of anemia in their studies was as shown in above table.…”
Section: Evaluation Of Hematological Parameters Rbc Parameterssupporting
confidence: 91%
“…Similarly, Tripathi et al reported mean hematocrit of 27.36% and it was found to be 31.31% in a study by Parinitha et al [9,13] Red cell distribution width: In the present study, Mean value of RDW-CV was found to be 15.67±2.59% in group A and 14.56±1.70% in Group B, which was in concordance to study conducted by Enawgaw et al and Parinitha et al in treatment naïve HIV reactive patients. [9,14] [15] 69.17% 51.15% Mathews et al [16] 45.3%…”
Section: Evaluation Of Hematological Parameters Rbc Parametersmentioning
confidence: 99%
“…15 Although gender, age, weight and clinical stage have reported as risk factor for anemia in HIV patients in previous studies, 1,3,4,16 in the present study did not find as risk factor. However, the level of Hb before based ART has been found as risk factor in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…The results showed that the prevalence of anaemia in the combined group was 40.7%. However, higher prevalence rates of 60.61% and 64.0% were observed in Benin City, South-south, Nigeria [23] and in Keffi Northcentral, Nigeria [24] respectively. A lower prevalence rate of 23% has been recently reported from Ghana [7].…”
Section: Discussionmentioning
confidence: 84%